Ultrafast all-optical clock recovery based on phase-only linear optical filtering - Maram, Reza; Kong, Deming; Galili, Michael; Oxenløwe, Leif Katsuo; Azaña, José (Optics letters, 2014)
We report on a novel, efficient technique for all-optical clock recovery from RZ-OOK data signals based on spectral phase-only (all-pass) optical filtering. This technique significantly enhances both the recovered optical clock quality and energy efficiency in comparison with conventional amplitude optical filtering approaches using a Fabry-Perot filter. The proposed concept is validated through recovery of the optical clock from a 640 Gbit/s RZ-OOK data signal using a commercial linear optical waveshaper.